The study of neural antibodies in neurology: A practical summary - Fernández-Fournier, Mireya; Lacruz, Laura; Nozal, Pilar; Chico, Juan Luis; Tallón Barranco, Antonio; Otero-Ortega, Laura; Corral, Iñigo; Carrasco, Angela (Frontiers in Immunology, 2022)
The field of Autoimmune Neurology is expanding rapidly, with new neural antibodies being identified each year. However, these disorders remain rare. Deciding when to test for these antibodies, when and what samples are to be obtained, how to handle and study them correctly, and how to interpret test results, is complex. In this article we review current diagnostic techniques and provide a comprehensive explanation on the study of these patients, in an effort to help with correct diagnosis minimizing false positive and false negative results. We also propose routine storage of samples and referral of certain cases to specialized research laboratories.